Rural Income Dynamics in Post-Crisis Indonesia - Jan Priebe; Robert Rudolf; Stephan Klasen; Julian Weisbrod (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
Indonesia is, what the World Development Report 2008 calls, a transforming country characterized by increasing rural-urban income disparities and high poverty rates. Bearing these facts in mind, it is striking how little is known about causes and mechanism of the underlying determinants of poverty in rural Indonesia. In this study we aim to shed more light on the determinants of rural incomes and poverty in Indonesia. Drawing on a unique and highly detailed rural household panel data set for Central Sulawesi we investigate what are the drivers of rural income growth. Moreover, exploiting the panel structure of our data set we are able to control explicitly for individual- and time-specific effects and for endogeneity issues in our estimations. In addition, in order to identify whether our findings might hold lessons for all of Indonesia, we upscale our analysis to the national level by comparing our results with the national household data survey SUSENAS. Our results indicate that a sharp increase in rural incomes took place in the post-crisis period. Moreover, the ability to alleviate poverty and to enjoy income growth has been strongly associated with a household's ability to diversify into the non-farm sector of the economy, to focus on higher value-added agricultural activities and its ability to invest into new production techniques. These results seem to hold for most of rural Indonesia and are robust to various model specifications.
Keywords: O12; O18; Q12; R20; 330; Rural non-farm income; agricultural productivity growth; rural poverty